Incidência de Sclerotinia sclerotiorum em feijoeiro (Phaseolus vulgaris L.) na região serrana do estado do Espírito Santo - Figueiredo dos Santos, Álvaro; Athayde, José Tadeu (Revista Ceres, 2025)
Sclerotinia sclerotiorum (Lib.) De Bary (= Whetzelinia sclerotiorum (Lib.) KORF and DUMONT) is pathogenic on a great number of economically valuable plants with a recorded host list of 383 species in 64 families.